Extraction and analysis of physical and chemical properties of açaí oil (Euterpe oleracea Mart.) (Research, Society and Development, 2021)
The açaí palm (Euterpeoleracea Mart.) is a palm tree native to the Amazon, which occurs in large extensions in the Amazon estuary. During the process of conservation and oil extraction, factors such as humidity, temperature, lipid enzymes and the presence of light can affect the lipid profile, favoring hydrolysis and releasing fatty acids. The presence of fatty acids influences the quality of oils. This work had as objective the extraction of açaí oil by organic solvent and the analysis of some physical-chemical parameters such as: density, acidity levels, and glycidic profile. For the extraction, soxhlet apparatus and hexane as solvent were used. The extraction of açaí oil did not show good yield, due to the choice of using whole fruits that have large amounts of fibers wrapped in the seeds. Density was analyzed using an ANTON PAAR 35n densimeter, acidity was measured by KOH titration and for the glycidic profile, the oil was submitted to Fourier Transform Infrared Spectroscopy (FTIR) analysis using the IR Prestige- 21 of Shimadzu. Density was a little low. The acidity level showed slightly high values, indicating the formation of fatty acids, in the glyceride profile it was possible to observe the presence of free fatty acids, which justifies the high acidity.